Asuhan Keperawatan Psikososial pada Ibu Nifas dalam Menghadapi Asi Belum Keluar Pada 0-3 Hari Pascasalin - Sherly Jeniawaty; Sri Utami; Queen Khoirun Nisa’ Mairo (Universitas Airlangga, 2016)
Introduction: The first factor as forming expectations was past experience. Familiarity with nursing care services would increase the likelihood of a realist expectations. Previous experience gave rise to more detailed knowledge about the services and promoting expectations about nursing care for post partum and breastfeeding period. This study aimed to explore the experiences and expectations of psychosocial nursing care for mothers in the postpartum period in order to deal with breast milk has not come out in 0-3 days postnatal in Public Health Center of Tanah Kali Kedinding Surabaya. Method: This qualitatif study used hermaneutic-phenomenological approach. Subjects were women with postpartum period was more of 3 days to 2 weeks after delivery. Samples were selected by purposive sampling technique. Data was processed using analysis of collaizi. Results: Results are grouped into the experience felt “physical and psychological complaints” when the milk has not come out, and expectation on psychosocial nursing care in order to deal with breast milk has not come out. Discussion: Furthermore, it was concluded that psychosocial nursing care given when the milk has not come out, can become mother’s experiences in order to achieve sustainability of successful breastfeeding.